Analisis Pengetahuan, Sikap Dan Perilaku Keuangan Terhadap Literasi Keuangan Mahasiswa Di Kota Batam - Agnes Mulyani; Dian Efriyenti (Prosiding, 2023)
The ease of using money makes it difficult for people to control their finances, financial management is always related to the necessities of life. Managing finances properly requires financial knowledge, attitudes, and behavior in using money. Financial difficulties are not only caused by a small income but due to person's inability to manage finances. Therefore, it is necessary to improve and develop habits to plan and manage finances. This study aims to examine the level of financial knowledge, attitudes, and financial behavior. This study used the solving formula for sampling with a tolerance level of 0.05 and obtained a sample of 282 respondents. The data collection technique used a questionnaire while the answers used a Likert scale. Several analyzes were performed: descriptive statistical analysis, data quality test, classical assumptions, influence, and hypothesis testing. The results showed that financial knowledge had a significant effect on financial literacy with significant level of 0.003 <0.05. Financial attitude has no significant effect on financial literacy with a significant level of 0.278 > 0.05. Financial behavior has significant effect on financial literacy with significant level of 0.001 < 0.05 and simultaneously knowledge, attitudes and financial behavior affect the financial literacy of students in Batam city.